PROFIL DAN PRODUKTIVITAS PUBLIKASI KARYA ILMIAH INTERNASIONAL CIVITAS PERGURUAN TINGGI DI SCOPUS : STUDI KASUS LIMA BESAR PERGURUAN TINGGI INDONESIA BERDASARKAN PERINGKAT WEBOMETRIC - Rulina Rachmawati; Tupan Tupan (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2017)
Research on profile and productivity  of international scholarly publication indexed by Scopus of top five universities by webometrics (Gadjah Mada University, University of Indonesia, Bandung Institute of Technology, Bogor Agricultural Institute, and Brawijaya University) had been done. Data were collected by searching through Scopus database, using “Indonesia” as keyword on affiliation search and publication of five universities was chosen from 2006-2016. The obtained data were the number of publications per year, the number of publications by fields of research, the authors collaboration between countries, and the authors collaboration between institutions. The top ten research subjects, authors collaboration between countries, and author collaboration between institutions were determined and analyzed by statistics and  descriptive method using microsoft excel and the result displayed in graphs and tables. Results showed that the number of international publications has increased significantly. Bandung Institute of Technology having the most publications and followed consecutively by University of Indonesia, Gadjah Mada University, Bogor Agricultural Institute and Brawijaya University. Research subject illustrated the research trend produced by institutions. Most publications produced by Bandung Institute of Technology were in engineering, while Bogor Agricultural Institute produced mostly in agricultural and biological Sciences. The most collaborating country were Japan, Malaysia, Australia, USA, and Netherland. Collaboration between countries and collaboration between agencies could be motivated by factors such as geographical proximity and numerous advantages which can get form research collaboration.